Research progress of Traditional Chinese Medicine comprehensive therapy in the treatment of acute lactational mastitis at early stage (哺乳期急性乳腺炎初期中医综合治疗的研究进展) - FAN Dongpan (范东盼); CHEN Hong (陈宏) (中西医结合护理)
This paper reviewed studies on Traditional Chinese Medicine comprehensive treatment of acute lactational mastitis at early stage. Based on the Traditional Chinese Medicine syndrome differentiation, the Traditional Chinese Medicine comprehensive treatment could be divided into oral administration and external application, and most common interventions adopted in the clinical practice were manual expression, Huolong Cupping therapy and moxibustion, Gua Sha, collaterals pricking and cupping. The majority of researches were clinical observations and case reports, and there is a need of research with more sample size and standard methodology. (本文对近五年来关于哺乳期急性乳腺炎初期的中医综合治疗方法及效果的研究进行总结。在中医辨证理论指导下, 分为中药内服, 中药外敷, 以及手法排乳、火龙罐综合灸、刮痧、刺络放血拔罐等干预为主, 且研究以临床观察为主, 个案形式展现居多, 样本量小, 缺乏规范统一的方式方法。)